Epidemiology of Sepsis in Children Admitted to PICUs in South America*. Issue 8 (August 2016) - de Souza, Daniela Carla; Shieh, Huei Hsin; Barreira, Eliane Roseli; Ventura, Andrea Maria Cordeiro; Bousso, Albert; Troster, Eduardo Juan
Abstract : Objectives: To report the prevalence of sepsis within the first 24 hours at admission and the PICU sepsis-related mortality among critically ill children admitted to PICU in South America. Design: A prospective multicenter cohort study. Setting: Twenty-one PICU, located in five South America countries. Patients: All children from 29 days to 17 years old admitted to the participating PICU between June 2011 and September 2011. Clinical, demographic, and laboratory data were registered within the first 24 hours at admission. Outcomes were registered upon PICU discharge or death. Interventions: None. Measurements and Main Results: Of the 1, 090 patients included in this study, 464 had sepsis. The prevalence of sepsis, severe sepsis, and septic shock were 42.6%, 25.9%, and 19.8%, respectively. The median age of sepsis patients was 11.6 months (interquartile range, 3.2–48.7) and 43% had one or more prior chronic condition. The prevalence of sepsis was higher in infants (50.4%) and lower in adolescents (1.9%). Sepsis-related mortality was 14.2% and was consistently higher with increased disease severity: 4.4% for sepsis, 12.3% for severe sepsis, and 23.1% for septic shock. Twenty-five percent of deaths occurred within the first 24 hours at PICU admission. Multivariate analysis showed that higher Pediatric Risk of Mortality and Pediatric Logistic Organ Dysfunction scores, the presence of two or more chronic conditions, and admission from pediatric wards were independently associated with death. Conclusions: We observed high prevalence of sepsis and sepsis-related mortality among this sample of children admitted to PICU in South America. Mortality was associated with greater severity of illness at admission and potentially associated with late PICU referral.